On Characterization Of B Focal Curves In E3 - Korpinar, Talat; Bas, Selcuk (Soc Paranaense Matematica, 2013)
In this paper, we study B focal curves in the Euclidean 3-space E-3. We characterize B-focal curves in terms of their focal curvatures.
Keywords: Bishop frame; Euclidean 3-space; Focal curve